Stem cell secretome attenuates acute rejection in rat lung allotransplant. (1st December 2018) - Pieróg, Jarosław; Fytianos, Kleanthis; Tamò, Luca; Simillion, Cedric; Taddeo, Adriano; Kocher, Gregor; Gugger, Mathias; Grodzki, Tomasz; Heller, Manfred; Blank, Fabian; Geiser, Thomas; Schmid, Ralph A; et al.
Abstract: OBJECTIVES: Stem cells secrete significant amounts of bioactive factors in their secretome that can be immunosuppressive. We studied the effect of the secretome obtained from bone marrow-derived mesenchymal stem cells (BMSC-sec) in combination with cyclosporine A following acute rejection of lung allografts in the rat. METHODS: Lung allotransplants were performed from male Brown Norway donor rats to recipient male Fisher 344 rats. Rat BMSC-sec was introduced intratracheally in the recipient every day after the transplant until the day the animal was sacrificed. Group A ( n  = 5) received control medium and cyclosporine A (2.5 mg/kg body weight intraperitoneally) for 5 days post-transplant and group B ( n  = 5) received BMSC-sec and cyclosporine A. Blood gas analysis was performed to assess graft function at day 5 only from the graft, and the tissue was sampled for measurement of the wet/dry ratio and histological grading of rejection. RESULTS: All control animals (group A) showed severe signs of rejection. At day 5 grafts in group B showed improved gas exchange (i.e. mean PaO2 mmHg 237.9 ± 130 mmHg vs 24.9 ± 7.8 mmHg in group A). Histological examination according to the International Society of Heart and Lung Transplantation (ISHLT) revealed moderate to severe rejection in all animals in group A (III B) and a significant improvement in group B (I–IIA). The wet/dry ratio was also reduced in group B to 6.19 ± 0.6 compared to 9.36 ± 2 in group A. Furthermore, in vitro T-cell proliferation was reduced after treatment with BMSC-sec for CD 3 cells (69.55 ± 07 vs 73 ± 0.84), for CD 4 (24.95 ± 1.2 vs 27.75 ± 0.21) and for CD 8 cells (3.75 ± 0.2 vs 5.68 ± 0.02). CONCLUSIONS: The BMSC-sec is a promising novel cell-based therapeutic option for acute rejection in a rat lung allograft model.